Improving the Quality of Civic Education Learning Through the Application of Audio-visual Media - Rahmawati, Eka Fitri; Yayuk Chayatun , Machsunah; Sutarum, Sutarum (Academia Publication, 2024)
This study aimed to improve the quality of learning through the application of audio-visual-based learning media. Using the ADDIE instructional design, the results of the study indicated that in achieving learning objectives, planning is an essential step in creating effective and efficient learning. Planning is an activity carried out by the teacher in the classroom before the lesson begins, starting with the analysis phase, which aims to identify potential causes of a performance gap in the learning process. The design phase aims to verify the learning capabilities and the appropriate teaching methods. The development phase aims to create and validate the chosen learning resources. The implementation phase is intended for the teacher to prepare the learning environment and engage students effectively in the learning process. The evaluation phase aims to assess the quality of the product and the teaching process, both before and after the implementation. This study produced an audio-visual learning media product to enhance the motivation and interest of 5th-grade students at SD Negeri 1 Kramat in Civic Education learning. Through the use of audio-visual learning media, students can engage with educational content in a more enjoyable and interactive way, enhancing their comprehension of the material. The findings of this study highlight the potential for such media to enrich the learning experience. It provides meaningful insights for teachers and policymakers focused on advancing education, as well as researchers in the field. Recommendations emphasize the importance of enhancing technical support, improving teacher competencies, and fostering better coordination to ensure the effective integration of instructional design-based learning media, ultimately aiming to elevate the quality of education in schools.